Case Report: Primary ciliary dyskinesia due to CCNO mutations: a Chinese pediatric case series and literature review - Tong, Lejun; Li, Li; Wang, Wenjian; Chen, Jiehua (Frontiers in Pediatrics, 2024)
Primary ciliary dyskinesia (PCD) is a hereditary disorder characterized by defects in cilia that impair mucociliary clearance. This study focuses on PCD caused by mutations in the CCNO gene and reports on three cases involving Chinese children. Case 1 was an 8-year-and-3-month-old boy who presented with respiratory distress after birth and later developed recurrent productive cough and purulent nasal discharge. He was initially diagnosed with diffuse panbronchiolitis (DPB) due to the presence of diffuse micronodules in lung CT scans. Case 2 was the younger sister of case 1. She also presented with respiratory distress shortly after birth, with a chest radiograph revealing atelectasis. She required oxygen supplementation until the age of 2 months. Case 3 was a 4-year-and-4-month-old girl with a history of neonatal pneumonia, persistent pulmonary atelectasis and recurrent lower respiratory tract infections. Her chest radiograph also showed diffuse micronodules. In all three cases, the final diagnosis of PCD was confirmed by genetic testing. Case 1 and 2 exhibited homozygous c.248_252dup TGCCC (p.G85Cfs*11) mutations in the CCNO gene, while case 3 harbored a homozygous c.258_262dup GGCCC (p.Q88Rfs*8) mutation. A literature review indicated that common clinical features of CCNO-PCD include neonatal respiratory distress (40/49, 81.6%), chronic cough (31/33, 93.9%), rhinosinusitis (30/35, 85.7%) bronchiectasis (26/35, 74.3%) and low nasal nitric oxide (nNO, 36/39, 92.3%). Notably, situs inversus has not been reported. In CCNO-PCD patients, cilia may appear structurally normal but were severely reduced in number or entirely absent. Lung CT scans in these patients may exhibit diffuse micronodules and "tree-in-bud" signs, which can lead to a clinical misdiagnosis of DPB. nNO screening combined with genetic testing is an optimized diagnostic strategy. Treatment options include the use of anti-infective and anti-inflammatory agents, along with daily airway clearance. This study underscores the importance of genetic testing in neonates and children with suspected PCD or those clinically diagnosed with DPB in order to enable early diagnosis and prompt intervention, thereby enhancing the prognosis for these patients.